Conversation Stations and Children Language Acquisition: A Case Study of a Four-Year-Old Child - Mohammad - Halili; Darul - Hikmah (Politeknik Negeri Padang, 2022)
Talking meaningfully and listening attentively to a child can be challenging for some. The practices, however, are pivotal to have children develop linguistically. Therefore, the purpose of this research is to study the impact of the implementation of conversation stations on a child language acquisition. This is a qualitative research which aims to explain a child’s linguistic phenomena. The linguistic aspects studied are designed in basic mental entities, covering naming objects, attributes and modifier, event, and attribute, modifier, and evaluation of the event. A four year and two-month old child as a participant engaged in the conversation stations and his utterances were noted for data selection and data analysis. This is helpful to recognize, identify, analyse, and draw a conclusion about how the child language acquisition is influenced by the implementation of the conversation stations. The current research demonstrates that the child is able to name the objects and later modify them properly, describe the events, and subsequently evaluate them, using more complex sentences instead of employing subject plus verb only and providing logical reasoning behind the arguments. It indicates that the conversation stations carry a meaningful practice to his oral language proficiency.